Differentials by Socioeconomic Status and Institutional Characteristics in Preventive Service Utilization by Older Persons in Costa Rica - Brenes Camacho, Gilbert (2009)
artículo (arbitrado)--Universidad de Costa Rica, Instituto de Investigaciones en Salud (INISA). 2009. Este documento es privado debido a limitaciones de derechos de autor